Comparison of two Radiometers in the Validation of the Irradiance Emitted in the Light Curing Apparatus of the Faculty of Medical Sciences and Health of Juiz De Fora /SUPREMA - Miranda, Dr. Diogo de Azevedo; Santos Souzai, Andressa dos; de Souza, Marianna Lessa; da Costa, Paula Bedeschi Roman (International Journal of Innovative Research in Medical Science, 2018)
Introduction: For better clinical execution, the performance of LED light curing agents is gaining space in dentistry. For a better efficiency of the photopolymerizers, the intensity of the light through the radiometers must be validated with the constant periodical maintenance so that the emission of light is within the standards of irradiance established by the manufacturers. Objective: To compare the irradiance measured by two Ecel RD-7 and SDI radiometers, respectively. Method: 8 Bluephase-based photopolymerizers were used when the batteries were fully charged. For each apparatus were measured three readings and then averaged. Results: The exploratory analysis of the data indicated homoscedasticity, that is, there is a significant difference between the variances of the two devices. Conclusion: The Ecel RD-7 radiometer with rechargeable battery presented better results than the SDI radiometer.